Mass Absorption Coefficient of Tungsten and Tantalum, 1450 eV to 2350 eV: Experiment, Theory, and Application - Levine, Zachary H. ([Gaithersburg, MD] : U.S. Dept. of Commerce, National Institute of Standards and Technology, 2003)
The mass absorption coefficients of tungsten and tantalum were measured with soft x-ray photons from 1450 eV to 2350 eV using an undulator source. This region includes the M3, M4, and M5 absorption edges. X-ray absorption fine structure was calculated within a real-space multiple scattering formalism; the predicted structure was observed for tungsten and to a lesser degree tantalum as well. Separately, the effects of dynamic screening were observed as shown by an atomic calculation within the relativistic time-dependent local-density approximation. Dynamic screening effects influence the spectra at the 25 % level and are observed for both tungsten and tantalum. We applied these results to characterize spatially-resolved spectra of a tungsten integrated circuit interconnect obtained using a scanning transmission x-ray microscope. The results indicate tungsten fiducial markers were deposited into silica trenches with a depths of 50 % and 60 % of the markers’ heights.